Widows’ Rights and Customary Law: Addressing Responsive Law to Divorce Cases of Tolaki Community in Indonesia - Kamaruddin, Kamaruddin (Mazahib, 2023)
This article discusses the tendency to ignore women's rights in customary law practices in the Tolaki tradition, Southeast Sulawesi, Indonesia. Women often become a victim of deprivation of rights by customary legal tradition, such as ex-wife rights in post-divorce and the right to make choices. This article aims to discuss how widows are protected by custom by offering responsive law as a process for resolving marriage and divorce through customary decisions. Normatively, legal divorce settlements can only be processed through religious court institutions. Using a normative-empirical approach, this study has three significant findings. First, the process of resolving family conflicts involves complying with applicable customary provisions that must be obeyed by the Tolaki community. Second, tradition is not the only basis for consideration in the elements for making customary decisions. Third, responsive law can theoretically direct the lives of the people of the Tolaki traditional community by providing recommendations for considerations that are in accordance with the social structure and community relations related to the application of customary law. However, according to custom, widows who are not resolved before a court hearing can be followed up again to immediately register their case in a religious court in order to minimize neglect of the right to terminate a unilateral divorce and the rights of the widow and children after divorce. Under these conditions, offering responsive law is a strategy to balance rights in divorce cases bound by state legal norms.